2016
DOI: 10.1002/dmrr.2798
|View full text |Cite
|
Sign up to set email alerts
|

Direct effects of exercise on kynurenine metabolism in people with normal glucose tolerance or type 2 diabetes

Abstract: Acute exercise directly affects circulating levels of tryptophan, kynurenine and kynurenic acid, providing a potential mechanism for the anti-depressive effects of exercise. Furthermore, exercise-mediated changes in kynurenine metabolism are preserved in type 2 diabetic patients. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 18 publications
10
43
0
1
Order By: Relevance
“…Indeed in our study, TNF mRNA was actually reduced in HFD‐fed mice. The only upregulated enzyme downstream in this pathway in HFD‐fed mice intestine was KMO, which may be consistent with an increased KMO in omental adipose tissue from obese women and higher kynurenine levels positively correlate with body mass index . In our studies, DIO mice had no change in intestinal mucosal tph1 expression, whereas in obese subjects TPH1 (Figure , Pathway 2) expression was increased in jejunum .…”
Section: Discussionsupporting
confidence: 85%
“…Indeed in our study, TNF mRNA was actually reduced in HFD‐fed mice. The only upregulated enzyme downstream in this pathway in HFD‐fed mice intestine was KMO, which may be consistent with an increased KMO in omental adipose tissue from obese women and higher kynurenine levels positively correlate with body mass index . In our studies, DIO mice had no change in intestinal mucosal tph1 expression, whereas in obese subjects TPH1 (Figure , Pathway 2) expression was increased in jejunum .…”
Section: Discussionsupporting
confidence: 85%
“…Diabetic retinopathy patients have elevated serum Kyn [72]. mRNA expression of KAT I and KAT II is modestly reduced in skeletal muscle from type 2 diabetic patients compared with that in normal glucose tolerant humans [73]. Exercise enhances KAT activity [73] may through upregulation of skeletal muscle KATs mediated by PGC-1α1 [22].…”
Section: Abnormal Kp and Risk Factors For Cvdmentioning
confidence: 99%
“…mRNA expression of KAT I and KAT II is modestly reduced in skeletal muscle from type 2 diabetic patients compared with that in normal glucose tolerant humans [73]. Exercise enhances KAT activity [73] may through upregulation of skeletal muscle KATs mediated by PGC-1α1 [22]. As expected, bariatric surgery is associated with the improvement and even the remission of T2D.…”
Section: Abnormal Kp and Risk Factors For Cvdmentioning
confidence: 99%
“…Most recently, Mudry et al reported a decline in kynurenine after exercise in humans, 28 suggesting that exercise-induced kynurenine degradation may be one of the reasons for lower kynurenine in those with higher muscle strength and functional capacity. In contrast, in most previous studies, inflammatory processes were regarded as the principal pathophysiological mechanism in patients with activated kynurenine pathway.…”
Section: Potential Mechanismsmentioning
confidence: 99%